A new model for state-of-the-art leadership education with performance as a driving factor for future viability - Werner G. Faix; Liane Windisch; Stefanie Kisgen; Laurentia Paradowski; Felix Unger; Wilfried Bergmann; Rudolf Tippelt (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
The challenges of today's rapidly changing environment are tremendous. Almost every organization has new tasks; some must even completely modify their objectives, strategy, business focus, or business model. In addition to the necessity of managing processes as effectively and efficiently as possible, the topic of leadership has gained increasing importance. Thus, training and development programs aimed at preparing future generations of leaders have long been well frequented. However, current leadership education fails to meet the demands of either the present or the future, as our analysis shows. For this article, we have thoroughly researched current leadership education programs and comprehensively studied the pertinent literature. Based on this, we recommend goals, content, and methods for a state-of-the-art leadership education program. Our main findings demonstrate that leadership education should focus on (1) the development of competencies and their demonstrated performance, (2) personal development, and (3) the implementation of real-world projects as a form of inquiry-based learning. Furthermore, we precisely describe an evidence-based approach for an innovative study program: the newly developed 'Diploma of Performance and Leadership' (DPL). We end by giving an outlook on the program's implementation, which will be accompanied by empirical evaluation.
Keywords: 330; Leadership; Leadership education; Innovation; Personality; Personal development; Competencies; Performance